Chewing capacity and ideal cardiovascular health in adulthood: A cross-sectional analysis of a population-based cohort study - Rangé, Hélène; Perier, Marie-Cécile; Boillot, Adrien; Offredo, Lucile; Lisan, Quentin; Guibout, Catherine; Thomas, Frédérique; Danchin, Nicolas; Boutouyrie, Pierre; Jouven, Xavier; Bouchard, Philippe; Empana, Jean-Philippe (Clinical nutrition (Edinburgh, Scotland), 2020)
To study the association between chewing capacity-a prerequisite for eating- and the level of cardiovascular health (CVH). This is a cross-sectional analysis conducted on 5430 study participants from the Paris Prospective Study 3 that were subjected to an oral examination by trained dentists at study recruitment between 2008 and 2012. Chewing capacity was determined by the number of functional tooth units (FTUs), and ≥ 5FTUs defined adequate chewing capacity. Subjects were categorized into poor, intermediate, or ideal CVH for the 4 behavioural (smoking status, body mass index, physical activity, diet) and the 3 biological (total cholesterol, fasting glycemia, and blood pressure) factors according to the American Heart Association Life's Simple 7. Multinomial logistic regression was used to explore the association between the number of FTUs (exposure) and ideal or intermediate vs. poor CVH (main outcome). 10.31% of the study participants had an ideal CVH and 7% presented an impaired chewing capacity (<5 FTUs). Subjects with at least 5 FTUs (OR = 2.37; 95% CI: 1.37–4.12) were more likely to have an ideal global CVH, after adjustment for age, sex, marital status, education, deprivation, depressive status, and dental plaque. This association existed for the behavioural but not the biological CVH, with the strongest association being observed with the diet metric. This is the first study suggesting that adults with a preserved chewing capacity have an increased likelihood to be at an ideal behavioural CVH. •Chewing capacity is a prerequisite for healthy eating.•Functional Tooth Units were associated with ideal cardiovascular health.•Behavioural component of ideal cardiovascular health was associated with FTUs.•Diet metric was the strongest associated metric with FTUs.•Replacing missing teeth preserve conditions associated with ideal cardiovascular health.